Vibrational relaxation and intersystem crossing of binuclear metal complexes in solution - van der Veen, Renske M; Cannizzo, Andrea; van Mourik, Frank; Vlček, Jr, Antonín; Chergui, Majed (Journal of the American Chemical Society, 2011)
The ultrafast vibrational-electronic relaxation upon excitation into the singlet (1)A(2u) (dσ*→pσ) excited state of the d(8)-d(8) binuclear complex [Pt(2)(P(2)O(5)H(2))(4)](4-) has been investigated in different solvents by femtosecond polychromatic fluorescence up-conversion and femtosecond broadband transient absorption (TA) spectroscopy. Both sets of data exhibit clear signatures of vibrational relaxation and wave packet oscillations of the Pt-Pt stretch vibration in the (1)A(2u) state with a period of 224 fs, that decay on a 1-2 ps time scale, and of intersystem crossing (ISC) into the (3)A(2u) state. The vibrational relaxation and ISC times exhibit a pronounced solvent dependence. We also extract from the TA measurements the spectral distribution of the wave packet at a given delay time, which reflects the distribution of Pt-Pt bond distances as a function of time, i.e., the structural dynamics of the system. We clearly establish the vibrational relaxation and coherence decay processes, and we demonstrate that PtPOP represents a clear example of a harmonic oscillator that does not comply with the optical Bloch description due to very efficient coherence transfer between vibronic levels. We conclude that a direct Pt-solvent energy dissipation channel accounts for the vibrational cooling in the singlet state. ISC from the (1)A(2u) to the (3)A(2u) state is induced by spin-vibronic coupling with a higher-lying triplet state and/or (transient) symmetry breaking in the (1)A(2u) excited state. The particular structure, energetics, and symmetry of the molecule play a decisive role in determining the relatively slow rate of ISC, despite the large spin-orbit coupling strength of the Pt atoms.